La presenza di Gustaw Herling-Grudziński sui quotidiani italiani - Ajres, Alessandro (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The Italian language Herling used after his move to Italy in 1955 was not only the language of everyday communication; it was also the language in which, from a certain point on, he wrote all his articles for Italian magazines and newspapers. The author retained Polish for the novels, essays, and short notes in his Dziennik (Journal written at night), as if to connect his native language with “real writing”; at the same time, he utilized Italian in his journalistic works. Yet, the texts Herling wrote in this language offer truly exceptional material for analysis. They allow us to trace the successive stages of his rapprochement with the Italian world, as well as the influence Herling had (or not) on Italian public opinion. Furthermore, comparing the Italian writings with the Journal written at night reveals how often certain articles were repeated in both languages in similar, if not identical, form; this attests to the importance of certain themes in his work.